SNF‐VBP Penalizes Skilled Nursing Facilities with Negative Profit Margins - Sharma, H. (Health Serv Res, 2020)
RESEARCH OBJECTIVE: Skilled Nursing Facility‐Value‐based Purchasing Program (SNF‐VBP) from the Centers of Medicare and Medicaid Services (CMS) incentivizes facilities to improve quality through lower hospital readmissions. However, SNF‐VBP may penalize nursing homes that are unable to invest resources to reduce readmissions. Although existing research has examined facility characteristics and SNF‐VBP performance, the relationship between financial performance and SNF‐VBP performance is unknown. In this study, we examine the SNF‐VBP performance by the financial performance of SNFs. STUDY DESIGN: We use data from three sources: 2019 SNF‐VBP performance data from CMS, and latest available CMS cost reports for SNFs (2017), and SNF characteristic data from LTCfocus.org (2017). We use descriptive methods to examine total profit margins and SNF‐VBP performance. We examine the characteristics of facilities with positive and negative profit margins, and within these, we further examine characteristics of facilities that are rewarded or penalized under SNF‐VBP. In the adjusted analysis, we evaluate the relationship between having a negative profit margin and experiencing penalty under the SNF‐VBP controlling for several SNF characteristics including resident acuity index, occupancy percentage, payer mix, size, profit status, chain membership, and market competition. POPULATION STUDIED: All freestanding SNFs with valid SNF‐VBP and cost report data (n = 12 420). PRINCIPAL FINDINGS: Of the 12 420 SNFs, about 46.4% have a negative profit margin. Furthermore, there is a 14‐percentage point difference in average profit margins for SNFs with positive profit margins vs. SNFs with negative profit margins (6.1% vs −8.15%). About 74.5% of SNFs with negative profit margins and 71.7% of the SNFs with positive profit margins are penalized under SNF‐VBP (P < .05). Among the 9063 SNFs that are penalized, about 47.4% of the SNFs have negative profit margins with an average profit margin of −8.23%. These penalized SNFs with negative profit margins (n = 4295) have an average loss of $24 400 from SNF‐VBP (range: −$4 to −$170 000). In the adjusted analysis, the odds of being penalized under the SNF VBP program for SNFs with negative profit margins are 13% higher vs. SNFs with positive profit margins (OR: 1.13; 95% CI: 1.04‐1.23). CONCLUSIONS: SNFs with negative profit margins are more likely to be penalized under the SNF‐VBP. IMPLICATIONS FOR POLICY OR PRACTICE: Although we want to incentivize quality improvement through programs like SNF‐VBP, we need to ensure that SNFs with negative profit margins have the resources to improve. Facilities with negative profit margins that are penalized under SNF‐VBP have an average loss of $24 400—an amount that roughly approximates average annual salary of a certified nursing assistant, one of the key nursing home direct care staffs. These losses may further exacerbate quality problems in facilities that are already struggling. Alternative approaches to assist financially struggling SNFs may help them improve quality and perform better under SNF‐VBP.